ANALISIS PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KINERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PERAWAT INSTALASI RAWAT INAP RSUD TIPE B DI TEGAL - Erfa, Roro Kusnabilla; Wahidi, Kemala Rita; Aida, Mus (Lembaga Penerbitan Universitas Esa Unggul, 2023)
This research is based on the dynamics of service quality problems in 2020-2021 reflecting problems regarding the performance of nurses in inpatient rooms in serving patients. The purpose of this study was to obtain evidence of the effect of competence and training on the performance of nurses in inpatient installations, with work motivation as an intervening variable. The research design used a cross sectional study, with a population of 135 inpatient installation nurses. The sampling technique used the probability sample and used a saturated sample so that the entire population was sampled using a simple random sampling technique. The results of the study prove that competence and training have a positive and significant direct effect on work motivation and performance, work motivation has a positive and significant direct effect on performance, and work motivation has a positive role in mediating the relationship between competence and training on nurse performance. Competence and training programs provided by the organization, will have an impact on increasing higher performance, if there are motives from nurses in the form of responsibility, expectations for progress, the work itself, achievement and recognition, the existence of organizational support related to the work context as the basis for driving their willingness to carry out the tasks assigned to him.